An extended three-stage treatment to correct a severe skeletal and dental discrepancy - Moore Grahame J. (Sciendo, 1999)
A report of a case of extended treatment of a patient with severe mandibular retrognathism and an Angle Class II division I malocclusion. Initial fixed appliance treatment reduced incisor protrusion. A second phase utilising a Teuscher appliance achieved improved facial and dental relations through excellent mandibular growth. A third phase of fixed Edgewise treatment finalised dental relations.